Amber filter with self-administered near vision screening card / Saiful Azlan Rosli … [et al.] - Rosli, Saiful Azlan; Ahmad Rudin, Ahmad Mursyid; Ahmad, Azmir; Zainodin, Elly Liyana; Ai Hong, Chen (Research Innovation Business Unit, 2014)
Visibility is defined as the greatest distance at which an object can be seen and recognized in either daylight or at night when the general illumination is increased to a daylight level. Visibility can be influenced by several factors, which include colour and contrast. Previous studies, which investigates the effects of colour combinations to level of visibility and visual performance on road signs, found that there is a significant difference in the level of visibility with different colour combinations (p< 0.05). It is clearly understood that in our nature environment and work tasks, each factors described above are variable, which in turn varies the level of visibility. Based on the supportive evidence from previous studies, visual aid such as amber lens can be used as an application to improve the level of visibility of a person in his/her daily work tasks. The amber filters with the near vision screening card can improve people’s eyesight, thus generate substantial economic benefits, and can make a major contribution to Malaysian development. In addition to the filter, the card also consists a modified near vision test that can be selfadministered. This test acts as a simple do-it-yourself screening for near vision. This eventually leads to the users awareness of their own near vision problem. This is inline with the nation’s recommendations in GTP, to drive the high-income countries as well as generate the health and work performance. Previous Study: Ahmad, A., Chen, A., Zulkifli, S., & Rosli, S. A. (2013). UiTM study on road signs in Malaysiaâ€¯: The impact of information volume of road sign on level of visibility. International Journal of Enhanced Research in Science Technology & Engineering, 2(6), 38â€“41. Aladin, A. Z., Rosli, S. A., & Chen, A. (2012). Visibility Comparison of Colour Combinations Used in Road Sign Design. Universiti Teknologi MARA (UiTM). Publication in reviewed. Iranian Journal of Ophthalmology (IrJO). Rudin, A. M. A., Saliman, N. H., Rosli, S. A., & Ahmad, A. (2011). Enhancement of contrast sensitivity by wearing amber tinted lens between youth hockey player and non-hockey player. 2011 IEEE Colloquium on Humanities Science and Engineering, 902â€“906. doi:10.1109/CHUSER.2011.6163868.